2022
DOI: 10.3390/ijerph19074415
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of the Malay Version of the WHO-5 Well-Being Index: Reliability and Validity Evidence from a Sample of Type 2 Diabetes Mellitus Patients

Abstract: The translation and validation process of the WHO-5 Well-Being Index (WHO-5) into Malay is still not yet available. This study is the first psychometric evaluation of the Malay version of the WHO-5 in a sample of 127 primary care patients with type 2 diabetes mellitus. We evaluated the internal consistency and 5-week test–retest reliability of the WHO-5 Malay, and three aspects of its validity—first, the factorial validity in relation to the factor structure of the WHO-5 Malay; second, the concurrent validity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
5
8
0
Order By: Relevance
“…These results are indications that the one-factor structure estimates better regarding the well-being of adolescents. These findings are in agreement with previous validation studies [ 14 , 20 , 39 , 42 , 43 , 46 , 48 ]. This implies that the well-being of adolescents in Ghana could be explained by a single underlying trait likewise adolescents of other countries.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are indications that the one-factor structure estimates better regarding the well-being of adolescents. These findings are in agreement with previous validation studies [ 14 , 20 , 39 , 42 , 43 , 46 , 48 ]. This implies that the well-being of adolescents in Ghana could be explained by a single underlying trait likewise adolescents of other countries.…”
Section: Discussionsupporting
confidence: 94%
“…Since its first publication in 1998, the WHO-5 has been translated into more than 30 languages and has been used in research studies all over the world. In addition, the scale (WHO-5) has been applied in different fields/disciplines using different population groups with diverse health conditions including patients with cancer [ 15 , 16 ]; Type 1 and 2 diabetes [ 17 , 18 , 19 , 20 ]; depression [ 21 , 22 ]; suicidal behaviors [ 23 , 24 ]; cardiovascular disease (e.g., myocardial infarction patients) [ 25 , 26 ]; alcoholism and other substance use disorders [ 27 , 28 , 29 ]; geriatrics [ 30 ]; stroke [ 31 ]; sleep disturbances [ 32 ]; personality disorder [ 33 ]; grief [ 34 ]; and occupational psychology [ 35 ]. It has also been applied to adolescents and students [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The unidimensionality of the WHO-5 was confirmed through factor analysis, with values from 57.7% (for the Norwegian sample) to 72.5% (for the Chilean sample). Our findings are consistent with prior research founding a one-factor structure [ 7 , 52 ], indicating that the WHO-5 can be used to measure the well-being of nurses in different countries for cross-cultural investigations. Notably, as IRT DIF analysis revealed, the WHO-5 performed differently for the well-being construct in the Norwegian sample than for the Spanish and Chilean ones.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also indicated adequate negative correlations between well-being and anxiety, consistent with a previous study that found strong correlations between the WHO-5 Well-Being Index and anxiety [ 29 ]. Additionally, adequate negative correlations were found between well-being and depression, consistent with previous studies reporting that the WHO-5 correlated negatively with depression [ 28 , 47 , 48 , 49 , 50 , 51 , 52 ]. Together with the obtained internal consistency values, these findings support the construct validity of the well-being scale.…”
Section: Discussionsupporting
confidence: 89%
“…Twenty-two studies (n = 5,005) (44-46, 49, 51, 52, 56, 68, 70, 72, 74, 79, 81, 82, 84, 85, 91, 95, 98-100, 104) evaluated the relationship between empowerment-related constructs and general QoL in patients with T2DM. Specific patient empowerment scales were used in six studies (44-46, 49, 51, 52) while self-efficacy was used in the remaining sixteen studies (56,68,70,72,74,79,81,82,84,85,91,95,(98)(99)(100)104). One study (44) used ANOVA to quantify this association and was not included in the MA.…”
Section: The Association Between Empowerment-related Constructs and Q...mentioning
confidence: 99%